Total Rewards and Employee Retention in a Middle Eastern Context. (April 2019) - Alhmoud, Ayman; Rjoub, Husam
This article examines the influence of total rewards—comprising extrinsic, intrinsic, and social rewards—on employee retention in Islamic banks in Jordan, with particular focus on the employee perspective. A questionnaire is used to collect data from the study sample, which consists of 500 employees working in various Islamic banks across Jordan. The study hypotheses are then tested using partial least squares (PLS) technique by applying structural equation models (SEMs). Results show that extrinsic, intrinsic, and social rewards are all important factors in achieving employee retention. Interestingly, social rewards were shown to have the highest level of influence on employee retention. This research is new in the Jordanian context; it offers a deeper understanding of some of the most important factors in retaining talent and thereby increasing organizational productivity and competitive advantage. It furthermore provides new insights into the relationship between total rewards and employee retention within the context of the Middle East, a combination previously uncharted.